MUHAMMAD IQBAL SERTA IDE PEMBENTUKAN NEGARA PAKISTAN - Reni, Reni; Santalia, Indo; G, Wahyuddin (AL-URWATUL WUTSQA: Kajian Pendidikan Islam, 2022)
Pakistan is one of the countries used by Muslims in the world as a reference, where the State of Pakistan which since its inception has been called an Islamic State, where Pakistan is basically part of India which is known to be the majority of the Hindu population. Therefore, this study aims to better understand the description of the ideas of Sir Muhammad Iqbal who is known that the idea thinking to form the State of Pakistan and separate from India is from him. This study uses a qualitative approach with a study of previous literatures such as History Books, Scientific Works related to the subject being studied, and the history of the History of the Modern Islamic World. Muhammad Iqbal Born with the full name Muhammad Iqbal bin Muhamamd Nur bin Muhammad Rafiq, born in 1873 in Sialkot, Punjab India, who was born from a simple family but is obedient and disciplined in living his life as a Sufi, and this was instilled in him from childhood by his parents. He died in 1938. So his idea of realizing an Islamic state was expressed in 1930 at which time he was elected president of the Muslim League and received strong support from Muhammad Ali Jinnah.Keywords:Muhammad Iqbal, Muslim Ummah, Pakistan State, Conflict